2021
DOI: 10.1167/iovs.62.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Cytokine Profile of Patients With the Boston Keratoprosthesis Type 1: Comparing Patients With and Without Glaucoma

Abstract: Inflammatory cytokines are involved in glaucoma pathogenesis. The purpose is to compare cytokine levels in the tear film of Boston keratoprosthesis (KPro) patients with and without glaucoma, relative to controls, and correlate levels with clinical parameters. METHODS.This cross-sectional study enrolled 58 eyes (58 patients): 41 KPro eyes with glaucoma, 7 KPro eyes without glaucoma, and 10 healthy controls. Twenty-seven cytokines were measured by multiplex bead immunoassay. Intraocular pressure (IOP), cup-to-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…As mentioned earlier, several inflammatory cytokines in the aqueous humor of POAG patients have been found to be associated with increased retinal ganglion cell death and elevated IOP [ 22 , 23 ]. The link between ocular pressure and tear cytokine levels also shows a study by Geoffrion et al [ 20 ] that indicates an association between an IOP elevation and an increase in levels of IFNy and IL1β in tear fluid. In our study, however, the level of IOP does not seem to affect the composition of tears between the group of patients with normal IOP and IOP higher than 20 mmHg.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As mentioned earlier, several inflammatory cytokines in the aqueous humor of POAG patients have been found to be associated with increased retinal ganglion cell death and elevated IOP [ 22 , 23 ]. The link between ocular pressure and tear cytokine levels also shows a study by Geoffrion et al [ 20 ] that indicates an association between an IOP elevation and an increase in levels of IFNy and IL1β in tear fluid. In our study, however, the level of IOP does not seem to affect the composition of tears between the group of patients with normal IOP and IOP higher than 20 mmHg.…”
Section: Discussionmentioning
confidence: 60%
“…Tears hold an important place in cytokine research as markers of immunoinflammatory response in various eye diseases. This is supported by a result from study suggesting that elevated concentrations of certain inflammatory cytokines such as IL1β or TNFα in the aqueous humor of patients with eye disorders may diffuse from the retina to the anterior chamber where it may end up in the tear fluid through the optic-corneal button interface [ 19 , 20 ]. Most studies examining the levels of cytokines in tears of glaucoma patients do not distinguish between POAG and OHT diagnoses.…”
Section: Discussionmentioning
confidence: 82%
“…While inflammation may also have an important role in KPro‐associated glaucoma, no study has yet investigated ocular fluids from KPro patients with glaucoma. The objective of this study was to compare cytokine levels in the tear film of KPro patients with and without glaucoma, relative to controls and correlate levels with clinical parameters (Geoffrion, Robert, Chodosh, et al, 2021; Geoffrion, Robert, Di Polo, et al, 2021). The long‐term goal was to establish how clinical care can be best tailored to the KPro patient population to improve outcomes despite high prevalence of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…We wanted to determine whether this mouse model was a proper model to examine inflammatory mechanisms and retinal ganglion cell apoptosis involved in glaucomatous optic neuropathy after KPro surgery. We investigated whether it was feasible to establish a reproducible animal model of glaucoma post‐KPro with the hope to use it to validate human outcomes in the future (Geoffrion, Robert, Chodosh, et al, 2021; Geoffrion, Robert, Di Polo, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cytokines play an important role in glaucomatous optic neuropathy, but their role in KPro‐associated glaucoma is still unknown. By analysing tear fluid of KPro patients by multiplex bead immunoassay (paper V), we identified that cytokines TNF‐a, IL‐1b, FGF‐basic and IFN‐g were elevated in KPro patients with glaucoma compared to those without (Geoffrion et al, 2021a). These cytokines correlated with optic nerve excavation and IOP.…”
mentioning
confidence: 99%